Self Medication Practices Among Residents of Slum Areas of Qasimabad, Hyderabad (Medical Forum Monthly, 2024)
Background: Self medication is the practice of treating ailments with medicines which are available without prescription. There is a lot of public and professional concern about the irrational use of drugs.Objectives: To assess self medication practices among residents of urban slum areas of Taluka Qasimabad, District Hyderabad & to determine the underlying factors for it.Study Design: A community based descriptive cross sectional studyPlace and duration of Study: This study was carried out among residents of peri-urban areas of Taluka Qasimabad, District Hyderabad from 15th October 2012 to 15th December 2012.Materials and Methods: Study tools, sample size & sampling technique: Data was collected through questionnaire based interviews from responders. Three hundred & eighty five responders were selected by convenience sampling.Data Analysis: The prevalence of self medication was calculated in percentage. The qualitative & quantitative variables were analyzed in SPSS version 16 by applying various tests of significance.Results: Total three hundred & eighty five respondents participated in the study; among them 207 were practicing self medication. 57% of the subjects were in age group 18-30 years (p=0.04). There was male preponderance (90.3%) showing significant association with self medication practice (p=0.01). Easy availability of medicines was the main reason for self practice (62.8%); various analgesics were the most commonly used drugs (58.5%).Conclusions: Self medication is the common practice among peri-urban residents; availability of low cost drugs is one of the most important determinants for this practice.